Potential Content of Palm Oil at Various Levels of Loose Fruit in Oil Palm Circle - Murgianto, Fitrah; Edyson, Edyson; Ardiyanto, Adhy; Putra, Shadiar Kesuma; Prabowo, Lilik (Jurnal Agro Industri Perkebunan, 2021)
Harvesting fresh fruit bunches (FFB) is an important activity in the oil palm plantation industry. This study aimed to analyze the potential content of palm oil at the level of loose fruit that falls on the oil palm circle. Observations were made on five fresh fruit bunches with criteria 1, 3, and 5 respectively loose fruit per bunch that falls on the oil palm circle from oil palm trees that were 22, 16, 12, and 7 years old. All sample fresh fruit bunches were analyzed for potential oil to bunch ratio and oil to wet mesocarp ratio in the analytical laboratory of Bumitama Gunajaya Agro. Content of oil to wet mesocarp ratio in loose fruit 1, 3, and 5 were 48.50%, 51.98%, and 53.21% respectively. While the content of oil to bunch ratio in loose fruit 1, 3, and 5 were 24.19%, 25.52%, and 25.71% respectively. Based on variable of oil to wet mesocarp ratio, the highest potential for oil content occurs in ripe palm fruit with a level of five loose fruit   per bunch that falls on that oil palm circle. Five loose fruit per bunch on the oil palm circle can be used as an indicator for harvesters to harvest ripe fruit with optimal oil content.